Molecular detection and characterization of Indian isolates of Pasteurella multocida serogroup 'A' - DUTTA, T K; GAUTAM, RAJEEV; SINGH, V P; KUMAR, A P (The Indian Journal of Animal Sciences, 2014)
Pasteurella multocida (serogroup 'A') isolates (18) from different animal hosts were tested for moleecular detection and characterization. All the isolates were identified by polymerase chain reaction (PCR) using primer pair KMTISP6-KMTIT7 giving approximately 450 bp amplified products. All the isolates were charaeterized by restriction endonuclease analysis (REA) and random amplified polymorphic DNA (RAPD)- PCR assays. Out of 7 isolates of serotype A: 1, 5 and 6 different REA partterns were observed after digestion wtih enzyme Hpa I and Hpa OO respectively. Similarly, out of 9 isolates of serotype A: 3,4 different REA patterns were produced by enxyme Hpa II respectively. RAPD-PCR was performed using singly primer OPG-13. Three different banding patterns were found from both A:3 and A:1 serotypes. Both the techniques were highly effective for charcterization of Pasteurella multocida isolates.Â